2011
DOI: 10.1002/ijc.25809
|View full text |Cite
|
Sign up to set email alerts
|

Intercountry prevalences and practices of betel‐quid use in south, southeast and eastern asia regions and associated oral preneoplastic disorders: An international collaborative study by asian betel‐quid consortium of south and east Asia

Abstract: Health risks stemming from betel-quid (BQ) chewing are frequently overlooked by people. Updated epidemiological data on the increased BQ use among Asian populations using comparable data collection methods have not been widely available. To investigate the prevalence, patterns of practice and associated types of oral preneoplastic disorders, an intercountry Asian Betelquid Consortium study (the ABC study) was conducted for Taiwan, Mainland China, Malaysia, Indonesia, Nepal and Sri Lanka. A random sample of 8,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
154
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(160 citation statements)
references
References 28 publications
4
154
0
2
Order By: Relevance
“…Another way is wrapping the areca nut and slaked lime in betel leaf with additions of tobacco and sweeteners or condiments. In contrast, among the Taiwanese the unripe areca nut is chewed together with slaked lime in which sometimes the betel leaf is added, however tobacco is never incorporated into the quid (Wen et al, 2005;Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way is wrapping the areca nut and slaked lime in betel leaf with additions of tobacco and sweeteners or condiments. In contrast, among the Taiwanese the unripe areca nut is chewed together with slaked lime in which sometimes the betel leaf is added, however tobacco is never incorporated into the quid (Wen et al, 2005;Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In some populations, tobacco is also added to the quid. A recent study by the Asian Betel Quid Consortium of South and East Asia found that Nepal had the highest prevalence of betel quid chewing (with tobacco), with Indonesia being the second highest, while all chewers from Taiwan and Mainland China chewed betel quid without tobacco (Lee et al, 2011). In Indonesia, betel quid chewing is practiced for the most part in rural areas and it is historically practiced by elderly females as a way of showing appreciation when guests come visiting, or during festivities such as weddings and cultural events.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, it has been ranked as the fourth most popular substance of abuse in the world and it is estimated that about 600 million people worldwide chew areca nut. 4 In one of the studies, areca nut chewing was found to increase the risk of having obstructive coronary artery disease by 3.5-fold. 5 There has been a lot of debate on whether betel nut chewing can lead to development of cancers.…”
mentioning
confidence: 99%
“…6,7 In another study higher prevalence of oral preneoplastic conditions like lichen planus, submucous fibrosis and leukoplakia were observed in betel nut chewers. 4 In addition, areca nut extract was also found to worsen the ethanol induced gastric ulcers and produce significant gastric mucosal damage in rats. 8 Thus, Areca catechu nut chewing may have beneficial or detrimental effects on health, thereby acting as the proverbial 'double-edged sword'.…”
mentioning
confidence: 99%
“…The betel quid in Taiwan is chewed without tobacco and often chewed with inflorescence of piper betel and lime, but most chewers have cigarette smoking habits. 9 In a meta-analysis of nine case-control studies, the pooled odds ratio (95% CI) of …”
mentioning
confidence: 99%